ANALISIS QUALITY OF LIFE (QOL) PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN TERAPI ANTIDIABETIK ORAL DAN INSULIN: TINJAUAN PUSTAKA SISTEMATIS - Annisa Zahra Zhafirah (2020)
Diabetes Mellitus Type 2 is a chronic disease that requires medication throughout the patient's life to maintain blood sugar levels and prevent complications of hyperglycemia. The study was conducted to see the quality of life of type 2 diabetes mellitus patients who use oral monotherapy, insulin or a combination of oral antidiabetic drugs with insulin. This research method uses a systematic literature review, which is to collect evidence relevant to journal quality standards to answer research questions that are the focus of the researcher. The assessment of journal quality used the checklist of The Joanna Briggs Institue (JBI) Critical Apprasial tools and 6 cross sectional journals were obtained with with inclusion criteria for type 2 diabetes mellitus patients, ages 18 to 65 years, Indonesian and English journals from 2015 to 2020 cross sectional study design, using antidiabetic oral and or insulin, using a questionnaire to evaluate the quality of life of patients with type 2 diabetes mellitus and there are domains affected by treatment. The results of this study indicate that patients who use monotherapy in the form of metformin have the highest quality of life scores than patients with insulin therapy and combination therapy, especially in the domain of physical health and treatment satisfaction. Patients with combination therapy of OAD and insulin had a higher QoL score than single insulin patients, especially in the psychological domains, dietary satisfaction and energy.